Antimicrobial resistance and gene regulation in Enteroaggregative Escherichia coli from Egyptian children with diarrhoea: Similarities and differences. Issue 1 (31st December 2021) - Abdelwahab, Radwa; Yasir, Muhammad; Godfrey, Rita E.; Christie, Gabrielle S.; Element, Sarah J.; Saville, Faye; Hassan, Ehsan A.; Ahmed, Entsar H.; Abu-Faddan, Nagla H.; Daef, Enas A.; Busby, Stephen J. W.; Browning, Douglas F.
ABSTRACT: Enteroaggregative Escherichia coli (EAEC) is a common diarrhoeagenic human pathogen, isolated from patients in both developing and industrialized countries, that is becoming increasingly resistant to many frontline antibiotics. In this study, we screened 50 E. coli strains from children presenting with diarrhea at the outpatients clinic of Assiut University Children's Hospital, Egypt. We show that all of these isolates were resistant to multiple classes of antibiotics and identified two as being typical EAEC strains. Using whole genome sequencing, we determined that both isolates carried, amongst others, bla CTX-M and bla TEM antibiotic resistance genes, as well as many classical EAEC virulence determinants, including the transcriptional regulator, AggR. We demonstrate that the expression of these virulence determinants is dependent on AggR, including aar, which encodes for a repressor of AggR, Aar. Since biofilm formation is the hallmark of EAEC infection, we examined the effect of Aar overexpression on both biofilm formation and AggR-dependent gene expression. We show that whilst Aar has a minimal effect on AggR-dependent transcription it is able to completely disrupt biofilm formation, suggesting that Aar affects these two processes differently. Taken together, our results suggest a model for the induction of virulence gene expression in EAEC that may explain the ubiquity of EAEC in both sick and healthy individuals.